Extraordinary child : poems from a South Indian devotional genre - Richman, Paula (SHAPS library of translations., 1997)
For hundreds of years Tamil poets have been composing devotional texts in which they adopt the voice of a mother and address praises to an extraordinary child. The poems, called pillaittamil (literally "Tamil for a child"), form a major genre of Tamil literature. Since the twelfth century, when the first known pillaittamil was written in honor of a Chola king, many of these poems have been composed in praise of Murugan and South Indian goddesses, as well as saints and venerated monastic abbots.